Institutional diversity, policy niches, and smart grids: A review of the evolution of Smart Grid policy and practice in Ontario, Canada. (February 2018) - Winfield, Mark; Weiler, Scott
Abstract: Jurisdictions around the world are responding the to potential of smart grids in different ways. This paper employs a multi-level perspective approach to socio-technological transitions to examine why the Canadian province of Ontario has seen a relatively smooth transition of smart meter technologies from the niche to regime levels as compared with other Canadian provinces, and other jurisdictions in the United States, European Union, and Australia. The paper also examines the reasons for Ontario's advanced legislative and policy framework around Smart Grid development, relative to those of other provinces. The complex institutional landscape around electricity that has emerged in Ontario since the break-up of the province's monopoly utility Ontario Hydro in the late 1990s emerges as a significant factor in both outcomes. The role of the province's municipally-owned LDCs spell out "local distribution companies (LDCs) as the primary agents for smart meter deployment, as opposed to a dominant vertically integrated utility, appears to have had an important mediating effect on public opposition to smart meters. With respect to Smart Grid policy, the diversity of high capacity institutional actors that now define the province's electricity policy landscape has facilitated the emergence of several interagency policy development niches. In a manner consistent with the concept of technological niches in the socio-technical transitions literature, the interagency status of these policy niches has shielded them from the regime level selective pressures that would likely have existed in a more unified institutional structure, and empowered new policy ideas to move from the niche to regime levels. These outcomes have significant implications for the understanding of socio-technological transitions, particularly around the role of institutional complexity in the emergence of niches for technology and policy development purposes and in niche to regime level transitions.